Sustainable design and website use amongst AS/A2 Level design and technology student projects - Simmons, Peter (Design and Technology Education: An International Journal, 2008)
This paper examines current design thinking, and design practice within AS/A2 Level design and technology. The paper focuses on website use within AS/A2 Level design folio work, and the use of sustainable design websites. It reports the research data gathered from two trials, illustrating the engagement with sustainable design, websites and sustainable design websites within student design folio work. The paper gives several specific examples of current practice in these areas, highlighting current trends within AS/A2 Level design and technology education.